Principal authority and its oil compliance during the Covid-19 Pandemic (Case Study On Beba Fishing Community, Takalar Regency) - Arisnawawi Arisnawawi; Darmawan Salman; Rahmat Muhammad; Muhammad Sabiq (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2022)
The fishermen who were hit due to the Covid-19 pandemic did not destroy the Punggawa-Sawi collaboration in Beba, Takalar Regency. The obedience of the Sawi in choosing to stay with the Punggawa can no longer be seen as a relationship of material interests such as wages for work. Because the material benefits in their relationship in the midst of the pandemic have also fallen sharply like fishing communities in general. This study uses a qualitative method with case study analysis. Data was collected using observation techniques, in-depth interviews and documentation. The data analysis technique is done by reducing the data, presenting the data and drawing conclusions. The results of this study indicate that the Punggawa authority that is woven into the Punggawa-Sawi relationship in Beba is obtained traditionally. They are not bound by a set of officially promulgated regulations. Sawi's obedience to the retainer was not solely due to material interests. However, their obedience was based more on the characterization of Punggawa because of his generosity and the existence of a family or kinship relationship between Punggawa and Sawi. This condition makes the relationship between Punggawa and Sawi very strong so that it does not waver even in the Covid-19 pandemic.